Order policy for emergency medicine with return uncertainty in a closed-loop supply chain. - Wei Pan; Ying Guo; Wenji Zhang; Lei Jin; Shujie Liao (PLoS ONE, 2018)
Due to difficulties in accurately predicting the emergency timing and the magnitude of a disaster, operations for perishable emergency inventory planning often encounter expiration and shortage problems. In order to ease the expiration problem in emergency medicine preparation inventories, this paper investigates an emergency medicine closed-loop supply chain for returning unused items from an ERC (Emergency Reserve Center) to a hospital. To assure that the return strategy is meaningful, we propose a critical parameter that we term the latest return time, after which the remaining emergency medicine in the ERC cannot be returned to the hospital. In addition, the short lifetime of emergency products and uncertainty about demand time and demand quantity are also considered in this emergency inventory planning system. In analyzing the optimal ordering policies, we find that the two threshold values for the predefined return time, which affect the total costs, are not monotonous; rather, the direction of their effect is first down, then up, and then down again, which means that a better predefined value of the latest return time can be determined by minimizing total costs. By studying and comparing decentralized and centralized decisions, we find that the centralized decision system works better to control expiration and costs. Therefore, we design a coordination mechanism for the cooperation between the ERC and the hospital. Our analysis shows that we should not ignore the emergency uncertainty and perishability of emergency items.